Modified zn o photocatalyst and its application in photocatalytic hydrogen production

CN118807814BActive Publication Date: 2026-11-03HUAZHONG AGRI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410901239.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2026-11-03
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

ZnO photocatalysts suffer from poor light absorption, easy electron-hole pair recombination, and excessively wide or narrow band gaps during photocatalytic hydrogen production, which limit their photocatalytic activity.

Method used

By preparing nanotube-shaped ZnO and constructing a ZnO/ZnS heterojunction, followed by Cd2+ substitution and N and Cu doping, a ZnO/CdZnS heterojunction is formed, and its photocatalytic performance is optimized.

Benefits of technology

It significantly improved the photocatalytic activity of ZnO, with the highest H2 evolution rate reaching 8.78 mmol·g-1·h-1, which is about 67.5 times higher than that of monomeric ZnO, and also showed good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118807814B_ABST
    Figure CN118807814B_ABST
Patent Text Reader

Abstract

The application discloses a modified ZnO photocatalyst and belongs to the field of photocatalytic hydrogen production. First, a nanotubular Zn-containing precursor is prepared through a solvothermal method, and then nanotubular ZnO is obtained through annealing. Subsequently, the nanotubular ZnO is used as a carrier to construct a ZnO / CdZnS heterojunction by using an in-situ sulfidation method and an ion substitution method. Due to the construction of the nanotube and the heterojunction, the photocatalytic H2 evolution rate of the ZnO / CdZnS heterojunction can reach 4.37 mmol·g ‑1 ·h ‑1 . Further, urea is used as an N source to introduce N doping into the ZnO and Cu doping into the CdZnS, and a N:ZnO / Cu:CdZnS heterojunction is designed and constructed. Due to the N and Cu doping, the photocatalytic H2 evolution rate of the N:ZnO / Cu:CdZnS heterojunction can reach 8.78 mmol·g ‑1 ·h ‑1 ·h . The application improves the photocatalytic performance of the ZnO and has a good application prospect in the field of photocatalytic hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalytic hydrogen production, and relates to a modified ZnO photocatalyst and its application in photocatalytic hydrogen production. Background Technology

[0002] Hydrogen is an ideal energy carrier with high energy density, environmental friendliness, and storability. How to efficiently generate hydrogen energy using solar power has become a popular research area for addressing the energy crisis. In 1972, the University of Tokyo in Japan accidentally discovered in a scientific experiment that TiO2 photoelectrodes, when irradiated with ultraviolet light, could promote the decomposition of H2O into H2 and O2. Following this groundbreaking discovery, researchers have continuously expanded and deepened semiconductor photocatalysis technology, successfully developing an increasing number of photocatalytic materials.

[0003] An ideal photocatalyst should possess a suitable band structure, high redox potential, good photocatalytic stability, low cost, and be easy to obtain and prepare. However, single photocatalytic materials often suffer from poor light absorption, easy photocorrosion, easy recombination of photogenerated electron-hole pairs, and excessively wide or narrow band gaps, which limit the efficiency of photocatalytic materials in practical applications. ZnO has advantages such as a suitable band structure, high charge migration rate, and excellent chemical stability, and is currently the most widely used material in the field of photocatalysis. However, ZnO still has some inherent disadvantages, such as: (1) the wide band gap of ZnO means that it only absorbs the ultraviolet region of sunlight, and the ultraviolet region accounts for only 5% of the solar spectrum; (2) electron-hole pairs in ZnO are very prone to rapid recombination, which limits the ability to diffuse to the catalyst surface, resulting in poor photocatalytic activity. These drawbacks greatly limit the application range of ZnO and its photocatalytic hydrogen production activity.

[0004] Based on this, the present invention improves the photocatalytic hydrogen production performance of ZnO by preparing nanotube-shaped ZnO to control the morphology / size of the material and constructing ZnO / ZnS heterojunction and performing element doping. Summary of the Invention

[0005] The purpose of this invention is to provide a modified ZnO photocatalyst and its application in photocatalytic hydrogen production, aiming to improve the photocatalytic activity of ZnO photocatalyst.

[0006] To achieve the above objectives, the present invention proposes the following technical solution: A modified ZnO photocatalyst is produced by using nanotube-shaped ZnO as raw material, generating a ZnO / ZnS heterojunction through in-situ sulfidation, followed by Cd oxidation. 2+ The ZnO / CdZnS heterojunction is formed by substitution.

[0007] The preparation method of the nanotube-shaped ZnO includes the following steps: 1) Reaction of zinc gluconate with diethylene glycol produces a Zn-containing precursor; 2) The Zn-containing precursor was subjected to high-temperature annealing to obtain nanotube-shaped ZnO.

[0008] The in-situ sulfidation involves reacting nanotube-shaped ZnO with thioacetamide. Preferably, the reaction temperature of the nanotube-shaped ZnO with thioacetamide is 60-100 °C, and the reaction time is 10-60 min.

[0009] Wherein, the Cd 2+ The substitution involves reacting the ZnO / ZnS heterojunction with cadmium acetate. Preferably, the reaction temperature of the ZnO / ZnS heterojunction with cadmium acetate is 140-180 °C, and the reaction time is 30-60 min.

[0010] Furthermore, the modified ZnO photocatalyst is based on a ZnO / CdZnS heterojunction, in which N-doping and Cu-doping are performed on the ZnO / CdZnS heterojunction to form an N:ZnO / Cu:CdZnS heterojunction. The preparation method includes the following steps: 1) Preparation of nanotube-shaped ZnO; 2) Disperse urea into nanotube ZnO and perform high-temperature annealing to obtain N-doped nanotube ZnO (N:ZnO). 3) React N-doped nanotube ZnO with thioacetamide to obtain N-doped nanotube ZnO / ZnS heterojunction (N:ZnO / ZnS). 4) React N-doped nanotube ZnO / ZnS heterojunction with cadmium acetate to obtain N-doped nanotube ZnO / CdZnS heterojunction (N:ZnO / CdZnS). 5) Copper acetate was dispersed into an N-doped nanotube ZnO / CdZnS heterojunction and reacted to obtain an N-doped nanotube ZnO / copper-doped CdZnS heterojunction (N:ZnO / Cu:CdZnS).

[0011] In step 2), the mass ratio of the nanotube-shaped ZnO to urea is 3-8:1-5, and the annealing temperature is 400-600℃.

[0012] In step 5), the mass ratio of the N-doped nanotube ZnO / CdZnS heterojunction to copper acetate is 100-200:1.

[0013] According to a specific embodiment of the present invention, a preferred method for preparing a modified ZnO photocatalyst is as follows: 1) Zinc gluconate and diethylene glycol were hydrothermally reacted at 180 °C for 24 h to generate a Zn-containing precursor. The Zn-containing precursor was then subjected to high-temperature annealing at 400 °C to obtain nanotube-shaped ZnO. 2) Disperse urea into nanotube-shaped ZnO, wherein the mass ratio of nanotube-shaped ZnO to urea is 5:3, and then perform high-temperature annealing treatment at 500 °C to obtain N-doped nanotube-shaped ZnO (N:ZnO). 3) N-doped nanotube ZnO and thioacetamide were reacted in water at a mass ratio of 1:1 at a reaction temperature of 80℃ for 30 min to obtain N-doped nanotube ZnO / ZnS heterojunction (N:ZnO / ZnS). 4) The N-doped nanotube ZnO / ZnS heterojunction was reacted with cadmium acetate at a mass ratio of 5:4 at a reaction temperature of 160 °C for 45 min to obtain the N-doped nanotube ZnO / CdZnS heterojunction (N:ZnO / CdZnS). 5) Copper acetate was dispersed into an N-doped nanotube ZnO / CdZnS heterojunction, wherein the mass ratio of the N-doped nanotube ZnO / CdZnS heterojunction to copper acetate was 150:1. The mixture was then reacted at a temperature of 160 °C for 45 min to obtain an N-doped nanotube ZnO / copper-doped CdZnS heterojunction (N:ZnO / Cu:CdZnS).

[0014] The modified ZnO photocatalyst provided by this invention can be applied to photocatalytic hydrogen production.

[0015] The present invention further provides a photocatalytic hydrogen production method, comprising the following steps: adding the modified ZnO photocatalyst to water, and using Na2S and Na2SO3 as sacrificial agents to carry out the photocatalytic hydrogen production reaction under an argon atmosphere.

[0016] The beneficial effects of this invention are: The ZnO / CdZnS heterojunction prepared in this invention achieves a photocatalytic H2 evolution rate of up to 4.37 mmol·g. -1 ·h -1 The yield is approximately 33.6 times higher than that of monomeric ZnO. Furthermore, multiple cyclic experiments demonstrated that ZnO / CdZnS exhibits excellent stability.

[0017] By doping ZnO / CdZnS heterojunctions with N and Cu, the highest photocatalytic H2 evolution rate of the prepared N:ZnO / Cu:CdZnS heterojunction can reach 8.78 mmol·g. -1 ·h -1The photocatalytic activity is approximately 67.5 times that of monomeric ZnO and 2.0 times that of the ZnO / CdZnS heterojunction, exhibiting a significantly enhanced photocatalytic ability. Furthermore, multiple cycle experiments demonstrated that N:ZnO / Cu:CdZnS possesses excellent stability.

[0018] The modified ZnO photocatalyst provided by this invention has a promising application prospect in the field of photocatalytic hydrogen production.

[0019] For more detailed technical solutions, please refer to the specific embodiments. Attached Figure Description

[0020] Figure 1 XRD patterns of ZnO / ZnS and ZnO / CdZnS-X series samples.

[0021] Figure 2 : TEM image (a) ZnO / ZnS-30, (b) ZnO / CdZnS-45; SEM image (c) ZnO / ZnS-30, (d) ZnO / CdZnS-45.

[0022] Figure 3 (a) HRTEM image and (b) SAED image of ZnO / CdZnS-45.

[0023] Figure 4 ZnO and ZnO / ZnS heterojunctions with different sulfidation times: (a) Trend of photocatalytic hydrogen production over time; (b) Comparison of photocatalytic hydrogen production rates of different samples.

[0024] Figure 5 : ZnO, ZnO / ZnS-30, different Cd 2+ (a) Trend of photocatalytic hydrogen production over time in ZnO / CdZnS-X heterojunctions with substitution time; (b) Comparison of photocatalytic hydrogen production rates of different samples.

[0025] Figure 6 (a) Cyclic stability determination of ZnO / CdZnS-45; (b) TEM of the sample after photocatalytic reaction; (c) XRD comparison of the sample before and after photocatalytic reaction.

[0026] Figure 7 (a) Trend graph of photocatalytic hydrogen production yield over time for ZnO, ZnO / ZnS, and ZnO / CdZnS before and after N doping; (b) Bar graph of photocatalytic H2 evolution rate before and after N doping.

[0027] Figure 8(a) Trend of photocatalytic hydrogen production over time for N:ZnO / CdZnS with different Cu doping amounts; (b) Bar chart of photocatalytic H2 evolution rate.

[0028] Figure 9 Cyclic stability determination graph of N:ZnO / Cu:CdZnS-0.2. Detailed Implementation

[0029] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.

[0030] Example 1: Design, construction, and photocatalytic hydrogen production performance study of ZnO / CdZnS nanotube heterojunctions. Zinc oxide (ZnO) is a widely used material in the field of photocatalysis due to its excellent electron carrying capacity, superior chemical stability, and suitable band structure. However, the wide bandgap of ZnO means that it only absorbs in the ultraviolet region of sunlight, and the rapid recombination of electron-hole pairs in ZnO also leads to low conversion efficiency, thus affecting its photocatalytic activity.

[0031] To address these two persistent problems, efficient light absorption can be achieved by rationally designing and controlling the morphology and size of ZnO materials, thereby enhancing photocatalytic activity. Furthermore, constructing heterojunctions with other materials can create favorable interfaces and synergistic effects, which help improve light absorption capacity and reduce the recombination rate of photogenerated carriers, thus increasing photocatalytic efficiency.

[0032] In morphology control, nanotube structures, with their high specific surface area and unique geometry, hold potential applications in photocatalysis. By synthesizing ZnO into nanotube structures, the presence of inner and outer walls exposes more active sites. Currently, there are few reports on the preparation of nanotube-shaped ZnO. Meanwhile, due to ZnS's more negative conduction band position, excellent electron mobility, and suitable band structure, this invention constructs a composite material to further improve photocatalytic performance.

[0033] 1. Material synthesis Synthesis of nanotubular Zn-containing precursors: Take 200 mg C 12 H 22 O 14Zn·xH₂O was dissolved in a 25 mL Erlenmeyer flask, and 0.5 mL of deionized water and 15 mL of diethylene glycol were added dropwise. The mixture was stirred for 15 min to obtain a homogeneous suspension. The resulting solution was then transferred to a 20 mL high-temperature, high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). The reactor was placed in a constant-temperature, forced-air drying oven at 180 °C for 24 h. After the reaction was complete, the reactor was removed and allowed to cool naturally to room temperature. The precipitate was then centrifuged (6000 r / min, 5 min) to obtain a brown precipitate. The precipitate was washed three times with deionized water and anhydrous ethanol (6000 r / min, 5 min), and the supernatant was discarded. The precipitate was then dried in a vacuum drying oven at 60 °C to obtain the Zn-containing precursor.

[0034] Synthesis of nanotube-shaped ZnO: A brown Zn-containing precursor was placed in a crucible and annealed in a muffle furnace at 400 °C in air for 0.5 h (heating rate 2 °C / min). After cooling to room temperature, white nanotube-shaped ZnO was obtained.

[0035] Preparation of nanotubular ZnO / ZnS heterojunctions: 25 mg of the prepared nanotubular ZnO and 25 mg of thioacetamide (TAA) were mixed with 10 mL of deionized water in a 50 mL round-bottom flask. After magnetic stirring for 15 min, the mixture was reacted in an oil bath at 80 ℃ for X min (X=15, 30, 45, 60). The products were separated by centrifugation, washed three times with deionized water and anhydrous ethanol (10000 r / min, 5 min), and the supernatant was discarded. The precipitates were dried in a vacuum drying oven at 60 ℃ to obtain ZnO / ZnS heterojunctions with different O / S ratios, denoted as ZnO / ZnS-X.

[0036] Preparation of nanotubular ZnO / CdZnS heterojunctions: 30 mg of ZnO / ZnS under optimal sulfidation conditions (i.e., ZnO / ZnS-30) and 24 mg of Cd(Ac)₂·2H₂O were mixed with 15 mL of ethylene glycol in a 25 mL Erlenmeyer flask. After magnetic stirring for 15 min, a homogeneous suspension was obtained. The mixture was then transferred to a 20 mL high-temperature, high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). The reactor was placed in a constant-temperature, forced-air drying oven and reacted at 160 °C for X min (X = 15, 30, 45, 60, 90). After the reaction was complete, the reaction vessel was removed and allowed to cool naturally to room temperature. The precipitate was obtained by centrifugation (10000 r / min, 5 min). The precipitate was washed three times with deionized water and anhydrous ethanol (10000 r / min, 5 min), and the supernatant was discarded. The precipitate was then dried in a vacuum drying oven at 60 ℃ to obtain different Cd concentrations. 2+The ZnO / CdZnS heterojunction with a certain content is denoted as ZnO / CdZnS-X.

[0037] Preparation of nanotube-shaped CdZnS: 25 mg of the prepared nanotube-shaped ZnO and 25 mg of thioacetamide (TAA) were mixed with 10 mL of deionized water in a 50 mL round-bottom flask. After magnetic stirring for 15 min, the mixture was reacted thoroughly in an oil bath at 80 °C for 6 h. The precipitate was then separated by centrifugation (10000 r / min, for 5 min) and dried in a vacuum drying oven at 60 °C to obtain nanotube-shaped ZnS. 30 mg of ZnS and 24 mg of Cd(Ac)₂·2H₂O were mixed with 15 mL of ethylene glycol in a 25 mL conical flask. After magnetic stirring for 15 min, a homogeneous suspension was obtained. The mixture was then transferred to a 20 mL high-temperature and high-pressure hydrothermal reactor lined with polytetrafluoroethylene. The reactor was placed in a constant-temperature drying oven at 160 °C for 45 min (optimal Cd...). 2+ (Replace time), that is, obtain CdZnS.

[0038] 2. Morphological and structural characterization For in-situ sulfidation of ZnO and further Cd 2+ The morphology and structural composition of the ZnO / ZnS-30 and ZnO / CdZnS-X heterojunctions obtained by substitution were studied. First, the phase composition and crystal structure of each heterojunction were analyzed by XRD characterization, such as... Figure 1 As shown, the ZnO / ZnS heterojunction exhibits weak peaks at 2θ = 31.4°, 34.2°, and 36.3°, while the strong peaks at 2θ = 28.5°, 47.6°, and 56.4° correspond one-to-one with the (008), (110), and (118) characteristic crystal planes of zincblende ZnS (PDF#05-0566). The decrease in the intensity of the ZnO diffraction peaks indicates a reduction in ZnO content and crystallinity after in-situ sulfidation. Therefore, it is indicated that during the sulfidation process, some ZnO crystals are transformed into ZnS crystals through in-situ growth, successfully forming a ZnO / ZnS heterojunction.

[0039] At the same time, compare different Cd 2+ The ZnO / CdZnS-30, ZnO / CdZnS-45, and ZnO / CdZnS-60 heterojunctions under different replacement times clearly show that with the change in Cd... 2+ The intensity of the characteristic ZnS diffraction peak at 2θ = 28.5° decreases with increasing replacement time, possibly due to the decrease in intensity of Cd. 2+ With increasing doping concentration, defects appear in the ZnS lattice, causing crystal expansion and a gradual increase in average grain size. This further verifies the doping properties of Cd. 2+The successful replacement. Furthermore, no impurity peaks were found in the diffraction patterns shown in the figure, indicating that the ZnO / ZnS and ZnO / CdZnS heterojunctions have high purity.

[0040] The ZnO / ZnS-30 and ZnO / CdZnS-45 heterojunctions prepared by in-situ sulfidation and ion substitution were also characterized by TEM and SEM. Figure 2 (a) It can be seen that the ZnO / ZnS-30 heterojunction prepared by the simple low-temperature oil bath method is a hollow tubular structure with a diameter of about 200 nm, which is similar to the morphology of ZnO. This indicates that ZnO retains its original hollow tubular structure after in-situ sulfidation. The in-situ sulfidation method causes the surface ZnO to undergo a thermal conversion reaction to generate ZnS in situ, without changing the original main structure. Figure 2 (c) is a SEM image of the ZnO / ZnS-30 heterojunction. As can be seen, the ZnO / ZnS-30 heterojunction exhibits a tubular structure. The hollow state of the heterojunction is more clearly observed through its fractured areas, and the morphology and size uniformity are good, thus avoiding significant variations in the material prepared after subsequent cation exchange due to significant differences between individual components. However, compared to ZnO, ZnO / ZnS-30 shows a relatively rough surface with fine particles, presumably tiny impurities formed during the sulfidation process. Figure 2 (b) ZnO / ZnS-30 heterojunction via Cd 2+ The TEM image of the ZnO / CdZnS-45 heterojunction formed after substitution shows that ZnO / CdZnS-45 still maintains a hollow tubular structure, and Cd... 2+ Substitution does not affect the overall structure of the hollow nanotubes. This indicates that despite the difference in the Zn / Cd ratio, the original structure of ZnO / ZnS-30 is largely preserved during ion exchange. Figure 2 (d) The SEM image of ZnO / CdZnS-45 also clearly shows that the pipe structure is slender, which is consistent with the results observed in the TEM image.

[0041] To further demonstrate the successful formation of ZnO / CdZnS heterojunctions via in-situ sulfidation and ion substitution, the microstructure properties of ZnO / CdZnS-45 were verified using high-resolution transmission electron microscopy (HRTEM), such as... Figure 3 As shown. By analyzing this Figure 3In (a), the lattice fringes reveal that the outer layer of ZnO / CdZnS-45 consists of densely packed, highly crystalline particles. The lattice spacing d = 0.28 nm corresponds to the (100) plane of ZnO, while d = 0.31 nm corresponds to the (101) plane and d = 0.32 nm corresponds to the (002) plane of CdZnS. The presence of these characteristic crystal planes strongly confirms the formation of a tight interface between ZnO and CdZnS, which is crucial for rapid carrier transport. Meanwhile, Figure 3 (b) shows two sets of diffraction spots selected by SAED, one mainly pointing to the (101) crystal plane of CdZnS, while the other can be attributed to the (100) crystal plane of ZnO. This further confirms the successful formation of ZnO / CdZnS heterojunction through in-situ sulfidation and cation substitution.

[0042] 3. Measurement of photocatalytic hydrogen production performance 20 mg of the synthesized catalyst powder was added to the photoreactor. Then, 0.35 mol / L Na₂S and 0.25 mol / L Na₂SO₃ were added to 100 mL of H₂O as sacrificial agents for the photocatalytic hydrogen production reaction. A magnetic stirrer was added, and the mixture was stirred thoroughly to ensure uniform dispersion of the photocatalyst. The vent valve of the reactor was opened, and argon gas was introduced into the reactor for 30 min to purge the existing air from the apparatus. Simultaneously, the magnetic stirrer was used to maintain stirring. Then, the vent valves on both sides of the photoreactor were closed to seal the reaction system. Cooling water was introduced to maintain the reaction system temperature at approximately 25 °C, with a light intensity of 180 mW / cm². 2 A 300 W xenon lamp was used as the light source for the photocatalytic hydrogen production reaction test. Samples were taken from the gas sampling port every 1 hour, and the hydrogen was quantitatively tested using a GC9790PLUS gas chromatograph from Zhejiang Fuli Analytical Instrument Co., Ltd. The test lasted for 4 hours, and the photocatalytic rate of the material was evaluated based on the hydrogen production rate.

[0043] First, the photocatalytic hydrogen production performance of ZnO / ZnS-X heterojunctions with different ZnO and ZnS composite ratios obtained under different sulfidation times (X=15 min, 30 min, 45 min, 60 min) was studied. Figure 4 (a) shows the trend of photocatalytic H2 production of each material over time. When the photocatalyst is irradiated by sunlight, due to the rapid recombination of photogenerated carriers, the original ZnO exhibits poor catalytic activity, with an H2 production rate of only 0.13 mmol·g. -1 ·h -1The figure shows that the hydrogen production rates of each material are as follows: ZnO / ZnS-30 > ZnO / ZnS-15 > ZnO / ZnS-45 > ZnO / ZnS-60 > ZnO. After introducing a small amount of sulfur source into the ZnO nanotubes, the hydrogen production of the ZnO / ZnS heterojunction gradually increases, and the hydrogen production activity is significantly improved. The effect of the homologous heterojunction between ZnO and ZnS improves the hydrogen production rate. - and h + The separation and transfer of H2 were observed. However, when the sulfidation time was extended to 45 min, the H2 production activity began to decrease; when the sulfidation time was 60 min, the H2 production activity showed a very significant decrease compared to sulfidation time of 30 min. This may be due to the relatively thick ZnS layer on the surface, which prevents light from reaching ZnO, thus weakening the function of the designed ZnS / ZnO heterojunction. Among these different photocatalysts, ZnO / ZnS-30 exhibited the best hydrogen production performance, with an H2 production rate of approximately 1.06 mmol·g⁻¹. -1 ·h -1 The H2 generation rate is approximately 8.2 times that of monomeric ZnO. This indicates that the synthesized ZnO / ZnS-30 heterostructure can significantly promote photoexcitation of e. - and h + The separation and migration of H2 effectively precipitates H2. These conclusions can be directly derived from... Figure 4 (b) shows a visual comparison of the photocatalytic hydrogen production rates of different samples in a bar graph. This study uses this ZnO / ZnS-30 heterojunction as a basis for subsequent Cd... 2+ Replace inquiry.

[0044] Following this, based on the ZnO / ZnS-30 heterojunction and Cd 2+ ZnO / CdZnS-X heterojunctions with different Cd / Zn ratios were prepared by varying substitution times (X=15, 30, 45, 60, 90). The H2 precipitation rate of the prepared ZnO / CdZnS-X heterojunctions was evaluated while keeping other test conditions constant. Figure 5 (a) shows the trend of H2 generation yield of each material over time. It is clear from the figure that the H2 precipitation increases linearly with increasing light irradiation time. However, the ZnO / ZnS-30 heterojunction exhibits lower photocatalytic activity due to the large band gaps of ZnS and ZnO, resulting in insufficient driving force for water splitting. The introduction of Cd... 2+ Subsequently, the H2 precipitation rate of ZnO / ZnCdS increased with Cd... 2+ The content increased significantly with the increase of Cd, which is due to the treatment of ZnS with Cd. 2+The exchange formation of a CdZnS solid solution broadened the light absorption region and successfully modulated the band structure of ZnS. The coexistence of multiple metal cations effectively increased the number of charge carriers and improved its conductivity. Due to its unique spatial distribution of photoexcited charge carriers, the hydrogen production rate was significantly increased compared to a single-phase structure. Figure 5 As clearly shown in (b), the hydrogen production performance of each material is as follows: ZnO / CdZnS-45 > ZnO / CdZnS-60 > ZnO / CdZnS-30 > ZnO / CdZnS-15 > ZnO / CdZnS-90 > ZnO / ZnS-30 > ZnO. Among these photocatalysts with different Zn / Cd ratios, ZnO / CdZnS-45 exhibits the best hydrogen production performance, with an H2 evolution rate of 4.37 mmol·g⁻¹. -1 ·h -1 The H2 generation rate is approximately 33.6 times that of monomeric ZnO and approximately 4.1 times that of the ZnO / ZnS-30 heterojunction, significantly improving the photocatalytic hydrogen production rate. However, as the Cd content continues to increase, excess CdS is formed. Since CdS possesses electrolytic activity... - with h + The inherent tendency for Cd to recombine actually reduces photocatalytic activity. These results indicate that by using Cd... 2+ The incorporation of ZnS to form a CdZnS solid solution, this unique ion exchange method further promotes the separation of photogenerated carriers, exhibiting a much higher photocatalytic H2 evolution capacity than the original ZnO / ZnS-30.

[0045] 4. Stability experiment of photocatalytic hydrogen production cycle After 4 hours of photocatalytic reaction, the xenon lamp was turned off, the valve of the photoreactor was opened to connect it to the atmosphere, and then argon gas was introduced into the reactor for 30 minutes to purge the gas in the device. After closing the valve, the photocatalytic reaction test was repeated. Each cycle test lasted 4 hours, and a total of 4 tests were conducted, for a total of 16 hours of photocatalytic reaction, in order to evaluate the photocatalytic stability of the photocatalyst.

[0046] Photocatalytic stability is also an important indicator for evaluating photocatalytic systems. After investigating the photocatalytic hydrogen production performance of the prepared samples and determining that ZnO / CdZnS-45 had the optimal photocatalytic activity, its photocatalytic stability was also studied. Figure 6 (a) shows the cyclic stability test of photocatalytic hydrogen production by ZnO / CdZnS-45. The figure shows that ZnO / CdZnS-45 maintained high catalytic activity even after 4 h cycles, 4 times, for a total of 16 h. Notably, the H2 production rate decreased from 4.59 mmol·g⁻¹ in the first test to the second test. -1 ·h -1Significantly increased to 5.26 mmol·g -1 ·h -1 The photocatalytic activity increased by approximately 14.59%. This improvement in photocatalytic activity is likely due to surface modification of the catalyst during cycling, which more fully exposes the active sites or enhances their surface reactivity, thereby improving both catalytic activity and stability. After the third and fourth cycles, the H2 production rate reached 5.31 mmol·g⁻¹, respectively. -1 ·h -1 5.30 mmol·g -1 ·h -1 The H2 generation rate did not decrease after the second cycle, indicating that ZnO / CdZnS-45 exhibits excellent photocatalytic stability. Further TEM characterization of the ZnO / CdZnS-45 after the photocatalytic reaction was performed, as shown below. Figure 6 As shown in (b), the heterojunction retains its hollow nanotube structure with a diameter of approximately 200 nm, consistent with observations made via TEM before the photoreaction. This is further supported by... Figure 6 (c) XRD characterization of the ZnO / CdZnS-45 heterojunction after photoreaction shows that the strong peaks at 2θ = 28.5°, 47.6°, and 56.4° correspond one-to-one with the characteristic crystal planes of wurtzite ZnO (PDF#36-1451) and zincblende ZnS (PDF#05-0566), with no impurity peaks or significant shifts. This indicates that the heterojunction has good crystallinity, and its chemical composition and crystal structure remain unchanged. Based on the above analysis, it can be determined that the designed and constructed ZnO / CdZnS-45 heterojunction exhibits excellent stability before and after photoreaction.

[0047] summary In this embodiment, a nanotube-shaped Zn-containing precursor was first prepared using a simple and optimized solvothermal method. After annealing, nanotube-shaped ZnO was obtained. Then, using the nanotube-shaped ZnO as a support, nanotube-shaped ZnO / CdZnS heterojunctions were synthesized via in-situ sulfidation and ion exchange. The nanotube structure was verified by morphology analysis using TEM and SEM. HRTEM and elemental mapping characterization confirmed the successful construction of the ZnO / CdZnS heterojunction. Thanks to the construction of the hollow tubular and Z-shaped heterojunctions, the optimal sample ZnO / CdZnS-45 heterojunction achieved a photocatalytic H2 evolution rate of 4.37 mmol·g⁻¹. -1 ·h -1 The yield is approximately 33.6 times higher than that of monomeric ZnO. Furthermore, multiple cyclic experiments demonstrated that ZnO / CdZnS exhibits excellent stability.

[0048] In summary, the ZnO / CdZnS-45 heterojunction obtained through in-situ sulfidation and ion exchange methods exhibits high photocatalytic performance and excellent stability. This method also demonstrates the significant potential of ion exchange in regulating carrier behavior at the heterojunction interface, enabling the realization of high-performance heterojunction structures through ion exchange engineering. This work represents a significant and innovative breakthrough in the design and control of nanotube-shaped ZnO photocatalysts.

[0049] Example 2: Design, Construction, and Photocatalytic Hydrogen Production Performance Study of N:ZnO / Cu:CdZnS Nanotube Heterojunctions Modifying the bandgap structure through doping is a common method for semiconductor modification. This primarily involves doping with non-metallic elements (N, C, S) or transition metal elements (Fe, Co, Mn, Cu) to reduce the bandgap and thus broaden the response range to the solar spectrum. Non-metallic doping techniques utilize the higher p-orbital energy levels of other non-metallic elements to replace the O 2p orbitals in wide-bandgap oxide semiconductors, thereby shifting the valence band top upwards and ultimately reducing the bandgap width.

[0050] Unlike non-metal doping, metal ion doping aims to introduce impurity energy levels into the band gap of wide-band semiconductors. These impurity energy levels are slightly lower than the conduction band bottom or slightly higher than the valence band top, allowing electrons to be excited by lower energies, thereby expanding the range of solar spectral response.

[0051] Based on the successful construction of ZnO / CdZnS described above, this embodiment introduces N doping into ZnO and Cu doping into CdZnS, and designs and constructs N:ZnO / Cu:CdZnS heterojunctions for the first time. The photocatalytic hydrogen production performance of N:ZnO / CdZnS, N:ZnO / Cu:CdZnS, and ZnO / Cu:CdZnS heterojunctions is also investigated.

[0052] 1. Material synthesis First, nanotube-shaped Zn-containing precursors were prepared and annealed to prepare nanotube-shaped ZnO, following the same method as in Example 1.

[0053] Synthesis of nanotubular N:ZnO: N-doped ZnO (N:ZnO) was prepared by calcination. First, 50 mg of ZnO was dispersed in 5 mL of ethanol and stirred at 350 r / min for 30 min until a homogeneous suspension was formed. Then, 30 mg of urea was added to the solution and stirred at 350 r / min for 2 h to disperse the urea. Next, the mixture was dried at 50 °C. Annealing was then performed in a muffle furnace at 500 °C in air for 2 h (heating rate 5 °C / min). After cooling to room temperature, N:ZnO was obtained.

[0054] Synthesis of nanotubular N:ZnO / ZnS heterojunctions: Using the optimal sulfidation method described in Example 1, 25 mg of the prepared N:ZnO material and 25 mg of thioacetamide were mixed with 10 mL of deionized water in a 50 mL round-bottom flask. After magnetic stirring for 15 min, the mixture was reacted in an oil bath at 80 °C for 30 min. The product was separated by centrifugation, washed three times with deionized water and anhydrous ethanol (10000 r / min, 5 min), and the supernatant was discarded. The resulting precipitate was dried in a vacuum drying oven at 60 °C to obtain the N-doped ZnO / ZnS heterojunction, denoted as N:ZnO / ZnS.

[0055] Synthesis of nanotubular N:ZnO / CdZnS heterojunctions: using the optimal Cd from Example 1 2+ The substitution method involves mixing 30 mg of N:ZnO / ZnS and 24 mg of Cd(Ac)₂·2H₂O with 15 mL of ethylene glycol in a 25 mL Erlenmeyer flask. After magnetic stirring for 15 min, a homogeneous suspension is obtained. This mixture is then transferred to a 20 mL high-temperature, high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). The reactor is placed in a constant-temperature drying oven at 160 °C for 45 min. After the reaction is complete, the reactor is removed and allowed to cool naturally to room temperature. The precipitate is then obtained by centrifugation (10000 r / min for 5 min), and the supernatant is discarded. The precipitate is dried in a vacuum drying oven at 60 °C to obtain the N:ZnO / CdZnS heterojunction, denoted as N:ZnO / CdZnS.

[0056] Synthesis of nanotubular N:ZnO / Cu:CdZnS heterojunctions: Based on the N:ZnO / CdZnS heterojunction, CdZnS was modified by Cu doping. 30 mg of N:ZnO / CdZnS and Y mg of Cu(Ac)₂·H₂O (Y = 0.1, 0.2, 0.3, 0.5) were mixed with 15 mL of ethylene glycol in a 25 mL Erlenmeyer flask. The resulting solution was then transferred to a 20 mL high-temperature, high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). The reactor was placed in a constant-temperature, forced-air drying oven at 160 °C for 45 min. The product was separated by centrifugation, and washed three times with deionized water and anhydrous ethanol (10000 r / min, 5 min). The supernatant was discarded, and the precipitate was dried in a vacuum drying oven at 60 ℃ to obtain the N:ZnO / Cu:CdZnS heterojunction, denoted as N:ZnO / Cu:CdZnS-Y.

[0057] Synthesis of nanotube-shaped ZnO / Cu:CdZnS-0.2: Based on the ZnO / CdZnS heterojunction in Example 1, CdZnS was modified by Cu doping. 30 mg of ZnO / CdZnS and 0.2 mg of Cu(Ac)₂·H₂O (optimal doping amount) were mixed with 15 mL of ethylene glycol in a 25 mL Erlenmeyer flask. The mixture was then transferred to a 20 mL high-temperature, high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). The reactor was placed in a constant-temperature drying oven at 160 °C for 45 min. The product was separated by centrifugation, washed three times with deionized water and anhydrous ethanol (10000 r / min, 5 min), the supernatant was discarded, and the resulting precipitate was dried in a vacuum drying oven at 60 °C to obtain the ZnO / Cu:CdZnS-0.2 heterojunction, denoted as ZnO / Cu:CdZnS-0.2.

[0058] 2. Measurement of photocatalytic hydrogen production performance The experimental method for photocatalytic hydrogen production is the same as in Example 1.

[0059] After studying and analyzing the morphology and structure of the material, simulated sunlight (300 W xenon lamp, light intensity: 180 mW / cm²) was used. 2 The hydrogen production performance of the prepared materials was evaluated with the participation of 0.35 mol / L Na2S / 0.25 mol / L Na2SO3 as sacrificial agents to consume holes. To investigate the effect of N doping on photocatalytic hydrogen production performance, N-doped N:ZnO, N:ZnO / ZnS, and N:ZnO / CdZnS were first prepared. Figure 7 (a) shows the corresponding trend of photocatalytic hydrogen production rate. When the photocatalyst is irradiated by sunlight, the pristine ZnO exhibits the worst photocatalytic activity, with an H2 production rate of only 0.13 mmol·g⁻¹. -1 ·h -1 Using urea as the nitrogen source and nano-ZnO as the support, the photocatalytic activity of the prepared N:ZnO was improved, with an H2 generation rate of approximately 0.21 mmol·g⁻¹. -1 ·h -1 The photocatalytic hydrogen production rate is approximately 1.6 times that of monomeric ZnO. This is because N doping can create lattice or surface defects, thereby increasing the generation and utilization efficiency of photogenerated electron-hole pairs and providing more active sites. The in-situ sulfidation method for constructing N:ZnO / ZnS from N:ZnO yielded a photocatalytic hydrogen production rate of 2.43 mmol·g⁻¹. -1 ·h -1 Compared to pure ZnO / ZnS (1.06 mmol·g), -1 ·h -1The efficiency was increased by approximately 2.3 times. This is attributed to the fact that N doping optimizes the electronic transport properties of ZnO, reducing the recombination effect between electrons and holes during in-situ sulfidation to form a heterojunction, thereby improving carrier lifetime and transport efficiency, and ultimately increasing the photocatalytic hydrogen production rate. 2+ By substitution, an N:ZnO / CdZnS heterojunction was constructed, which exhibited the best hydrogen production performance, with an H2 generation rate of approximately 5.79 mmol·g. -1 ·h -1 Compared to pure ZnO / CdZnS, the hydrogen production rate increased by approximately 1.3 times, and was about 44.5 times that of monomeric ZnO. This indicates that the N:ZnO / CdZnS heterojunction exhibits strong photogenerated electron-hole activity, and that N doping effectively enhances the photocatalytic activity. Figure 7 (b) is a bar chart comparing the photocatalytic hydrogen production rates of different materials. It can be seen that the materials constructed with urea as the N source and ZnO as the support exhibit superior photocatalytic activity compared to those without N doping.

[0060] Next, the N:ZnO / Cu:CdZnS-Y heterojunctions prepared with different Cu doping amounts (Y = 0.1 mg, 0.2 mg, 0.3 mg, 0.5 mg) in the N:ZnO / CdZnS heterojunction were discussed. While keeping other test conditions constant, the H2 precipitation performance of the prepared heterojunctions with different Cu doping amounts was evaluated, such as... Figure 8 As shown. Figure 8 (a) shows the trend of H2 photocatalytic generation for each material. It is clearly seen from the figure that the H2 precipitation increases linearly with increasing irradiation time. Further Cu doping of N:ZnO / CdZnS significantly increases the H2 precipitation rate with increasing Cu doping content, indicating that Cu doping of CdZnS successfully modulates the band structure of the material and promotes photocatalytic H2 generation. - with h + The migration of these particles enhances the separation efficiency of photogenerated carriers. Furthermore, a synergistic effect exists among the various metal cations, with interactions boosting the reaction rate and improving photocatalytic activity. From... Figure 8 As can be clearly seen in (b), the hydrogen production performance of each material is as follows: N:ZnO / Cu:CdZnS-0.2>N:ZnO / Cu:CdZnS-0.3>N:ZnO / Cu:CdZnS-0.5>N:ZnO / Cu:CdZnS-0.1>ZnO / Cu:CdZnS-0.2>ZnO / CdZnS. N:ZnO / CdZnS-0.2 exhibits the best hydrogen production performance, with an H2 evolution rate of 8.78 mmol·g. -1 ·h-1 The photocatalytic hydrogen evolution rate significantly surpassed that of monomeric ZnO, approximately 67.5 times that of ZnO, 2.0 times that of ZnO / CdZnS heterojunction, and 1.5 times that of N:ZnO / CdZnS heterojunction, exhibiting superior photocatalytic activity. However, with further increases in Cu content, the photocatalytic hydrogen evolution rate decreased. This may be due to excessive Cu doping, leading to excessive concentration or competition of active sites, which hinders the adsorption and reaction of reactants on the catalytic surface, affecting the photocatalytic reaction and reducing activity. These results indicate that the optimal Cu doping amount is 0.2 mg. To more clearly compare the effect of Cu doping on the photocatalytic performance of ZnO / CdZnS, a comparative material ZnO / Cu:CdZnS was synthesized, and its hydrogen evolution rate was tested to be 7.13 mmol·g⁻¹. -1 ·h -1 The hydrogen production rate is approximately 1.6 times that of pure ZnO / CdZnS. This indicates that introducing Cu doping into CdZnS promotes the hydrogen production of e. - with h + The migration of [the material] exhibits a higher photocatalytic H2 precipitation rate than that of the original ZnO / CdZnS.

[0061] After determining that N:ZnO / Cu:CdZnS-0.2 exhibited the best photocatalytic activity, its photocatalytic stability was further tested. For example... Figure 9 As shown, N:ZnO / Cu:CdZnS-0.2 maintained high catalytic activity even after 16 hours of reaction, with each cycle lasting 4 hours and repeated 4 times. After 4 cycles, it retained 98% of its activity, reflecting its good photocatalytic stability.

[0062] summary Building upon the successful construction of the ZnO / CdZnS heterojunction in the previous section, this embodiment introduces N doping into ZnO and Cu doping into CdZnS, thus designing and constructing the first N:ZnO / Cu:CdZnS heterojunction. Under simulated sunlight irradiation, using Na2S / Na2SO3 as a sacrificial agent, the N-doped N:ZnO / CdZnS heterojunction exhibits a performance of 5.79 mmol·g⁻¹. -1 ·h -1 The H2 generation rate was approximately 1.3 times higher than that of ZnO / CdZnS. Further Cu doping of N:ZnO / CdZnS resulted in an N:ZnO / Cu:CdZnS heterojunction, where the optimal sample achieved a photocatalytic H2 evolution rate of 8.78 mmol·g⁻¹. -1 ·h -1It exhibits a significantly enhanced photocatalytic activity, approximately 67.5 times that of monomeric ZnO, 2.0 times that of ZnO / CdZnS heterojunction, and 1.5 times that of N:ZnO / CdZnS heterojunction. Furthermore, multiple cycle experiments demonstrated that N:ZnO / Cu:CdZnS-0.2 possesses excellent stability.

[0063] In summary, the N:ZnO / Cu:CdZnS-0.2 heterojunction, after introducing N and Cu doping into ZnO / CdZnS, exhibits high photocatalytic performance and excellent stability, making it a promising candidate for application in the field of photocatalysis. This method also demonstrates that introducing non-metallic or metallic doping can effectively adjust the band structure of materials, optimize their photoelectric properties, and improve charge transport behavior, providing valuable insights and considerations for the design and construction of novel photocatalysts.

[0064] Appendix: Experimental Reagents

Claims

1. The application of a modified ZnO photocatalyst in photocatalytic hydrogen production, characterized in that, The preparation method of the modified ZnO photocatalyst includes the following steps: 1) Zinc gluconate was reacted with diethylene glycol to generate a Zn-containing precursor. The Zn-containing precursor was then subjected to high-temperature annealing to obtain nanotube-shaped ZnO. 2) Disperse urea into nanotube ZnO and perform high-temperature annealing to obtain N-doped nanotube ZnO (N:ZnO). 3) N-doped nanotube ZnO was reacted with thioacetamide at 80 °C for 30 min to obtain N-doped nanotube ZnO / ZnS heterojunction (N:ZnO / ZnS). 4) N-doped nanotube ZnO / ZnS heterojunction was reacted with cadmium acetate at 160 °C for 45 min to obtain N-doped nanotube ZnO / CdZnS heterojunction (N:ZnO / CdZnS). 5) Copper acetate was dispersed into an N-doped nanotube ZnO / CdZnS heterojunction and reacted to obtain an N-doped nanotube ZnO / copper-doped CdZnS heterojunction (N:ZnO / Cu:CdZnS).

2. The application as described in claim 1, characterized in that: In step 5), the mass ratio of the N-doped nanotube ZnO / CdZnS heterojunction to copper acetate is 100-200:

1.

3. A photocatalytic hydrogen production method, characterized in that: A modified ZnO photocatalyst is added to water, and Na2S and Na2SO3 are used as sacrificial agents to carry out a photocatalytic hydrogen production reaction under an argon atmosphere. The modified ZnO photocatalyst is prepared according to the method described in claim 1.

Citation Information

Patent Citations

  • Method for preparing zinc oxide nanotubes

    CN104386736A

  • Copper-doped Zn0. 5Cd0. 5S composite visible-light-driven photocatalyst as well as preparation method and application thereof

    CN117324008A